e-Tendering system for construction projects - Mohamed Elias, Ezanee; Mahidin, Norlila; Shiratuddin, Norshuhada (2003)
This project is carried out to develop a system. prototype of an electronic tendering (e-Tender) system. Several steps have been taken starting with information gathering and analyzing, developing a prototype, and ending in system testing. The prototype was further tested with real users to analyze the document flow speed. In conclusion, e-Tendering system has a better approach compared to the manual process of tender. The document flow speed was increased by 58.5% which suggests a more efficient process.